'I am greatly obliged to the Dutch': James Beattie's Dutch Connection. Issue 1 (March 2020) - Hengstmengel, Joost
Abstract : In the second half of the 18th century, Scottish Enlightenment philosophy spread to the Dutch Republic, where it found a favourable reception. The most popular Scottish philosopher among Dutch intellectuals arguably was James Beattie of Aberdeen. Almost all of his prose works were translated into Dutch, and the Zeeland Society of Sciences elected him a foreign honorary member. It made Beattie remark that he was 'greatly obliged to the Dutch', and a Dutch learned journal that he had 'in a sense become a native'. This article discusses why precisely the Dutch got interested in Beattie and what made his common sense philosophy appealing to a Dutch audience. It argues that it was the moderate and non-speculative nature of Beattie's moral philosophy that fitted well with the eclecticism of the Dutch Enlightenment.